Reappraisal of probiotics' safety in human. (July 2019) - Sotoudegan, Farzaneh; Daniali, Marzieh; Hassani, Shokoufeh; Nikfar, Shekoufeh; Abdollahi, Mohammad
Abstract: Contrary to the safe usage of probiotics for years, their threat is still worthy of attention. Several risks have been explained or mentioned in the case reports, clinical trials and experimental studies. Due to a large number of probiotic products worldwide, the certainty of the safety of such products is a matter of concern. Current review appraises all the available information about a range of adverse effects by probiotics in different populations of consumers and almost all qualified investigations and reports, relevant to the adverse effects of probiotics. Furthermore, the effects of basic or original sources of probiotics were studied. The principally noticed adverse effects of probiotics are systemic infections, gastrointestinal side effects, skin complications, inflammation of endocardium, gene transfer from probiotics to the normal microbial flora, metabolic harmful impacts of probiotics, and immune system stimulation. The most at-risk groups consist of infants, elderly people, patients in hospitalized condition, and those with immunodeficiency due to a genetic or acquired disease. The existing evidence suggests careful evaluation of the risk-benefit ratio of probiotics prior to prescription or recommendation to use. Highlights: Albeit probiotics have been indicated to be helpful in a variety of illnesses, they do not always appear to be without safety risks. Several studies indicated that probiotics are not completely safe. Some adverse effects by using them were observed. Immunocompromised patients, critically ill patients, people with cancer and infants are considered at risk. Prior to administration of probiotics, it is recommended to consider the benefit-risk.